KEPUASAN PELANGGAN ROOSTER ATAS KINERJA PELAYANAN ROOSTER PADA PERGURUAN TINGGI RAHARJA - Abas Sunarya; Untung Rahardja; Ayu Wanda (CCIT Journal, 2015)
Information service system currently has penetrated into the various elements one of which is college. Information service system has grown significantly with the increasing needs of customers for information. Of these needs we are required to always move forward and follow the development of information technology. However, the information service system ROOSTER there are some shortcomings that must be corrected to be the subject of research. Among the problems that there is a level of satisfaction of service performance Rooster. ROOSTER ("Role Online Ticketing System Raharja") is an information service by using the "online ticket" that the system is provided as a further container to accommodate question obtained operators iDuHelp!. This research data derived from questionnaires online (iSur) to the 20 respondents who had made at Rooster ticket. From the questionnaire online (iSur) concluded that the service Rooster effect on customer satisfaction. While customer satisfaction and trust are factors that affect the customer's intention to re-use the Rooster. The findings of this study indicate that overall customer satisfaction has a strong influence to re-use the Rooster.